If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3.2=b+(-0.2)
We simplify the equation to the form, which is simple to understand
-3.2=b+(-0.2)
Remove unnecessary parentheses
-3.2=+b-0.2
We move all terms containing b to the left and all other terms to the right.
-1b=-0.2+3.2
We simplify left and right side of the equation.
-1b=+3
We divide both sides of the equation by -01 to get b.
b=-3
| 6n+19n-7=0 | | z+=-13 | | a-14=18 | | m+8=14 | | m-1.2=-1.2 | | 50-k=80 | | 6x-9y=72 | | 3y^2-4=-4y | | 4(x+2)2-4=12 | | 2(x+7)=10 | | 9x^2+3kx-k=0 | | x^2-6x+3=k(2x-1) | | 15-5x=-25 | | 3x-9=42 | | 42-20=2p | | 3y^2-4=4y | | -4x-40-14x=32 | | C=Amt | | C=Amy | | x-x*0.2=y | | 3x^2-14x=5 | | 4k(k+3)=-19 | | 3-2=x+4 | | 5x+2(x+2)=18 | | 6x^2+11x=72 | | 4x^2-44x=-120 | | 3x+6=X+4 | | C=2500+0.5Yd | | 14+8.2= | | -2j+5=6h | | 3u-(25-u)=-11-2u | | Y=3mx-4b |